Processing of unconventional stimuli requires the recruitment of the non-specialized hemisphere - Kenett, Yoed N.; Anaki, David; Faust, Miriam (Frontiers in Human Neuroscience, 2015)
In the present study we investigate hemispheric processing of conventional and unconventional visual stimuli in the context of visual and verbal creative ability. In Experiment 1, we studied two unconventional visual recognition tasks – Mooney face and objects' silhouette recognition – and found a significant relationship between measures of verbal creativity and unconventional face recognition. In Experiment 2 we used the split visual field paradigm to investigate hemispheric processing of conventional and unconventional faces and its relation to verbal and visual characteristics of creativity. Results showed that while conventional faces were better processed by the specialized right hemisphere, unconventional faces were better processed by the non-specialized left hemisphere. In addition, only unconventional face processing by the non-specialized left hemisphere was related to verbal and visual measures of creative ability. Our findings demonstrate the role of the non-specialized hemisphere in processing unconventional stimuli and how it relates to creativity.